Sustainable Intensification Farmer Manual (Zambia & Southern Africa) - CGIAR Research Program on Maize (2021)
manual is based on the experiences of various sustainable intensification projects & the SIFAZ Project in Zambia. https://www.cgiar.org/research/publication/sustainable-intensification-practices-for-smallholder-farmers-in-zambia-a-farmers-manual See also follow-on project kicked off Oct 2020: https://www.cgiar.org/news-events/news/iita-and-cimmyt-collaborate-to-enhance-adoption-of-conservation-agriculture-in-southern-africa/